An overview of nanotechnology-based treatment approaches against Helicobacter Pylori - Safarov, Tural; Kiran, Bukre; Bagirova, Melahat; Allahverdiyev, Adil M.; Abamor, Emrah Sefik (TAYLOR & FRANCIS LTD, 2019)
Introduction: Helicobacter Pylori (H.Pylori) is a pathogen that infects about 50% of the world?s population and is known to be responsible for gastroduodenal diseases such as atrophic gastritis, peptic ulcer and stomach cancer. Nowadays, there is no treatment that ensures complete eradication. In addition, resistance to antibiotics used in the current treatment adversely affects the success rates in the fight against infection. Areas covered: This article take attention to treatment approaches using nanoparticles as an alternative to H.Pylori treatment to cope with increased antibiotic resistance. The purpose of this review is to provide an overview of the current limitations and new promising altenatives in treatment of H.Pylori, to highlight the location of nanotechnology to overcome treatment failures, and to emphasize the advantages of using membrane-coated nanoparticles for the first time. Expert opinion: Because of the current problems in the treatment of H.Pylori, there is increasing interest in alternative approaches including nanotechnology. The strong antibacterial effects of metallic nanoparticles, the advantages of polymeric nanoparticles in drug delivery and drug protection, and the prominent properties of membrane-coated nanoparticles in direct targeting demonstrate the significance of nanotechnology in developing new approaches for treatment of H.Pylori infection.
Keywords: Helicobacter Pylori; treatment; nanoparticles; drug delivery; cell membrane; coating; ANTIBIOTIC-RESISTANCE; SILVER NANOPARTICLES; ANTIBACTERIAL ACTIVITY; TRIPLE THERAPY; DRUG-DELIVERY; POLYMERIC NANOPARTICLES; GLIADIN NANOPARTICLES; METAL NANOPARTICLES; GOLD NANOPARTICLES; QUADRUPLE THERAPY; Infectious Diseases; Microbiology; Pharmacology & Pharmacy